2010
DOI: 10.1007/s10681-010-0273-1
|View full text |Cite
|
Sign up to set email alerts
|

Genetic distance and hybrid value in tropical maize under P stress and non stress conditions in acid soils

Abstract: An emphasis in maize breeding for areas with acid soils is the development of varieties with tolerance to P-deficiency plus high yield potential in acidic as well as normal soils. This study was carried out to assess the (i) genetic diversity within a set of tropical inbred lines developed from acid soil-tolerant populations; (ii) F1 yield performance, mid-parent heterosis (MPH), high-parent heterosis (HPH), and specific combining ability (SCA) in a diallel set of crosses under P stress (low P) and non-stress … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…However, it was not possible to observe a positive and significant correlation of genetic distance with heterosis or with the performance of lines per se considering such crosses (Table 2). George et al (11) suggested that the relationship between genetic distance and heterosis is not so simple since genetic distances between parental lineages can increase the level of heterosis to some point, after which heterosis tends to decline. In our study, the most distant lineages (JS-12 and São Mateus) did not present estimates of satisfactory heterosis for the analyzed characteristics.…”
Section: Resultsmentioning
confidence: 99%
“…However, it was not possible to observe a positive and significant correlation of genetic distance with heterosis or with the performance of lines per se considering such crosses (Table 2). George et al (11) suggested that the relationship between genetic distance and heterosis is not so simple since genetic distances between parental lineages can increase the level of heterosis to some point, after which heterosis tends to decline. In our study, the most distant lineages (JS-12 and São Mateus) did not present estimates of satisfactory heterosis for the analyzed characteristics.…”
Section: Resultsmentioning
confidence: 99%
“…We intend to explore heterosis among the three groups by crossing a set of inbred lines with desirable agronomic traits from different groups to determine the combining ability among inbred lines and to develop hybrids with high heterotic and yielding hybrids for Brazilian tropical conditions. Here, we recommend crosses between grouped inbred lines that are very divergent from inbred lines from opposite groups based on SNP genetic distances, since hybrid performance is higher when parents are genetically diverse [ 19 , 23 , 84 – 86 ]. Then, heterotic hybrids must be evaluated across several tropical environments in Brazil, and information on combining ability may be used to complement the grouping of inbred lines based on molecular markers, choice of testers and in the development of breeding populations and new inbred lines.…”
Section: Discussionmentioning
confidence: 99%
“…In this way, molecular markers have been extensively used to assess the genetic relationships, linkage disequilibrium (LD), population structure, and genetic diversity of breeding inbred lines in many maize breeding programs around the world. They have been successfully employed to: (i) assist in the selection of the best parental combinations for starting new pedigree populations [ 6 – 8 ], (ii) assign germplasm into heterotic groups [ 9 16 ], (iii) choose and replace testers [ 12 , 17 ], (iv) predict untested hybrids and avoid crosses between similar inbred lines [ 18 23 ], and (v) estimate the loss of genetic diversity during the breeding process [ 24 , 25 ]. According to Viana et al [ 21 ], the overall LD in the parental lines has a significant impact on the prediction accuracy of non-assessed single cross performance, mainly for crops showing unclear heterotic groups, such as tropical maize.…”
Section: Introductionmentioning
confidence: 99%
“…Only the fourth combination (ZPL1xZPL5) differed, as heterosis was very high (169.67%) and the yield somewhat lower (9.87 t/ha) than expected. Many authors have established a significant positive correlation between the genetic distance and heterosis (SRDIĆ et al, 2007;PAVLOV et al, 2016;GEORGE et al, 2011). GEORGE et al (2011) stated that the relationship between the genetic distance and heterosis was complex and that the level of heterosis increased with the increasing of the genetic distance, but only to a certain point after which it decreased.…”
Section: Resultsmentioning
confidence: 99%